KUALITAS OBJEK WISATA KOTA YOGYAKARTA BERDASARKAN DATA SCRAPING - Dwi Kunto Nurkukuh; Candra Ragil (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
During the COVID-19 pandemic, the tourism sector experienced a decline in visitor numbers. This served as a lesson for the tourism sector to increase visits once the pandemic ended. However, in 2023, during the holiday season, it was recorded that the Special Region of Yogyakarta (DIY) saw a decrease in visits compared to the previous year. This decline is believed to be due to many visitors shifting their tourism preferences to the city of Surakarta. Therefore, Yogyakarta City needs to evaluate the quality of its tourism. The purpose of this study is to assess the quality of Yogyakarta City's tourism based on data scraping. This research uses a descriptive qualitative approach with data scraping analysis using the Outscraper software. The data used are reviews from visitors to tourist attractions in Yogyakarta City. From the processed Google Maps reviews, the quality of the tourist attractions is categorized into the following tourism elements: 1)Attraction: The attractions in Yogyakarta City include culture, history, education, architecture, art, and children's playgrounds. While the attractions are diverse, natural attractions are still lacking. 2) Accessibility: Most of the attractions are located in the city center and are strategically placed, available on Google Maps. However, traffic conditions are congested, signage to tourist destinations and mobility within the attractions are still lacking. Entrance tickets are relatively affordable and match the attractions offered. Parking is generally available both within and around the attractions. 3) Amenities: The attractions are relatively close to accommodations, near other tourist spots, and have facilities such as toilets, places of worship, and culinary options. 4) Ancillary Services: The attractions are relatively clean and comfortable, with guides and staff available. However, some areas were found to have insufficient lighting and inadequate equipment maintenance.